Holiday s on the Map of Political Identity in Belorussia - M. O. Nikulina (Проблемы постсоветского пространства, 2017)
Modern political realities bring research issue of identity to the forefront. This aspect becomes of great importance in particular for the states of the post-Soviet space as well as in general for the whole region. Searching for new political traditions as well as “dividing” the existing ones along with the common historical past is obvious in the conditions of statehood formation. In this context the example of inner political variety of positions and approaches in Belorussia as in one of the active participants of the integration processes in the region is interesting. The attempts to define the area of the political identity in the Belorussian society are made in the article. The analysis of the official holidays shows main characteristics of political identity in Belorussia at the present stage. Different political and social forces perception of these events and attitude towards them are displayed. The basic and alternative trends of the further country development are defined through the lens of the significant dates and events.